Effective zakat management towards sustainability - Mohd Thas Thaker, Mohamed Asmy; Akbar, Mohamed Aslam; Mohammed, Mustafa Omar; Duasa, Jarita (Routledge, Taylor & Francis Group, 2024)
Islamic Social Finance Institutions (ISFIs) have rapidly expanded over the past decades. This impressive growth is seen largely from the perspective of collection and distribution, reflecting the non-profit-oriented nature of the business entities. Despite ISFIs’ expansion, critics are of the opinion that ISFIs place little emphasis on achieving the Maqasid al Shari’ah, in spite of commendable efforts by regulators in Malaysia in harmonizing the ISFIs industry towards Maqasid al Shari’ah. This study aspires to develop a Maqasid al Shari’ah-based index by operationalizing the Maqasid framework of Imam al Ghazali. Based on this, an index will be developed to measure the performance of ISFIs in Malaysia. This study contributes to the literature by harnessing Al Ghazali frameworks to develop an index with respect to ISFIs’ performance evaluation. The Maqasid index is vividly anticipated to help the stakeholders to measure the extent to which the performance of ISFIs in Malaysia is in line with Maqasid al Shari’ah. This study is critical in line with the Malaysian government’s aspiration to make Malaysia an international hub for ISFIs.